Knights & castles : exploring history through art - Martin, Alex. (Chanhassen, MN : Two-Can Pub., 2005)
Presents a collection of full-color paintings and illustrations depicting the lives of medieval knights on and off the battlefield, life on the land, hunting, festivals and children's games, and the joust.
Includes bibliographical references (p. 62) and index.
8.1
3-6
Keywords: Knights and knighthood -- Juvenile literature; Castles -- Juvenile literature; Civilization, Medieval -- Juvenile literature; Knights and knighthood; Castles; Civilization, Medieval; Knights and knighthood; Castles; Medieval civilization